2010
DOI: 10.1039/c0cc01763a
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpically driven peptide stabilization by protective osmolytes

Abstract: We determined the added enthalpic and entropic contributions of protective osmolytes to the folding of a model peptide into its native beta-hairpin state. In contrast to entropically driven steric "crowding", this study shows that sugars and polyols can act as protective osmolytes by primarily diminishing the unfavourable enthalpic contribution to folding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
141
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(163 citation statements)
references
References 25 publications
(18 reference statements)
18
141
0
Order By: Relevance
“…The second difficulty is that observed effects of osmolytes and crowders on protein binding and folding often have significant enthalpic contributions (23,(37)(38)(39). Excluded volume effects are entropic, whether treated by the mean-field AO, scaled particle, or HS mixture models.…”
Section: Discussionmentioning
confidence: 99%
“…The second difficulty is that observed effects of osmolytes and crowders on protein binding and folding often have significant enthalpic contributions (23,(37)(38)(39). Excluded volume effects are entropic, whether treated by the mean-field AO, scaled particle, or HS mixture models.…”
Section: Discussionmentioning
confidence: 99%
“…Using a β-hairpin peptide as a test molecule, the Harries group (Politi and Harries 2010;Sukenik et al 2012) observed stabilizing effects for small polyol osmolytes and the synthetic polymers, polyethylene glycol and dextran. The enthalpic components differed for the two classes of cosolute.…”
Section: Enthalpy and Entropymentioning
confidence: 99%
“…This effect is achieved because of the preferential exclusion of osmolytes from the protein interface that stabilizes protein states with smaller accessible surface area. 11,[13][14][15][16][17][18][19] Taken together, this wide range of cellular cosolutes presents a highly elaborate environment for the processes that lead to amyloid formation.…”
Section: Different Cosolutes Distinctively Affect Aggregation Kineticsmentioning
confidence: 99%
“…14,20,28 The cosolutes included polyols and PEGs of different molecular weights. The aggregation process was followed using several experimental techniques, including circular dichroism, electron microscopy and ThT fluorescence.…”
Section: Different Cosolutes Distinctively Affect Aggregation Kineticsmentioning
confidence: 99%